Technologies for agricultural transformation: Animal health - Grace, Delia (Routledge, 2019)
Countries in Southern Africa derive immense benefits from livestock production and demand for livestock products is set to increase in the coming decades. Rapid increase in livestock production brings opportunities but also increases vulnerability to animal disease and human health externalities such as antimicrobial resistance and unsafe food. Priority livestock diseases in Southern Africa include foot and mouth disease, peste des petits ruminants, trypanosomosis, anthrax, rabies and salmonellosis. As well as the impacts of disease on animals and people, concern is growing about the environmental impacts of livestock. Technologies have the potential to mitigate the risks and maximize benefits, including diagnostics, vaccines, antimicrobial alternatives, eAgriculture and prediction and modelling tools. Getting technologies to end-users requires packages that combine them with enabling policy and incentives. Sustainable intensification, progressive disease control and risk-based approaches to food safety are among the most important propositions. Government should support research-to-use through adopting One Health, promoting animal welfare and strengthening public and private veterinary services.